Liquid Water Transport Behavior at GDL-Channel Interface of a Wave-Like Channel - Ikechukwu S. Anyanwu (Energies, 2020)
This paper evaluates the liquid water at the gas diffusion layer-channel (GDL-channel) interface of reconstructed GDL microstructures with uniform and non-uniform fiber diameters in wave-like channels. A non-uniform GDL microstructure is reconstructed for the first time at the GDL-channel interface to evaluate droplet motion. The three-layer GDL microstructures are generated using the stochastic technique and implemented using the OpenFOAM computational fluid dynamics (CFD) software (OpenFOAM-6, OpenFOAM Foundation Ltd., London, UK). The present study considers the relationship between reconstructed GDL surfaces with varying fiber diameters, wettability, superficial inlet velocity and droplet size. Results show that the droplet detachment and the average droplet velocity decrease with an increase in the fiber diameter as well as the structural arrangement of the fibers. Under the non-uniform fiber arrangement, the removal rate of water droplets is not significantly improved. However, the choice of smaller fiber diameters facilitates the transport of droplets, as hydrophobicity increases even at slight surface roughness. The results also indicate that the average droplet velocity decreases under low inlet velocity conditions while increasing under high inlet velocity conditions. Therefore, the structural make-up of the GDL-channel interface influences the droplet dynamics, and the implementation of a non-uniform GDL structure should also be considered in the GDL designs.